2009
DOI: 10.1093/toxsci/kfp284
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice with a Constitutively Active Aryl Hydrocarbon Receptor Display a Gender-Specific Bone Phenotype

Abstract: Bone tissue homeostasis is governed by hormones, growth factors, and cytokines and can be distorted by environmental pollutants, such as ligands to the aryl hydrocarbon receptor (AhR). A transgenic mouse expressing a constitutively active aryl hydrocarbon receptor (CA-AhR), mimicking continuous low-dose exposure to AhR ligands, was used to explore potential long-term effects of these ligands on bone. The density, content, and dimensions of cortical and trabecular bone, as well as physical properties, were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 42 publications
1
20
2
Order By: Relevance
“…2E). These findings are opposite to what is seen in female Ahr −/− mice (19). Ahr activation leads to the induction of a number of genes regulating metabolism, most specifically genes encoding the Cyp1 enzymes.…”
Section: Resultscontrasting
confidence: 73%
“…2E). These findings are opposite to what is seen in female Ahr −/− mice (19). Ahr activation leads to the induction of a number of genes regulating metabolism, most specifically genes encoding the Cyp1 enzymes.…”
Section: Resultscontrasting
confidence: 73%
“…Our laboratory, and other groups that have more recently evaluated systemic AhR KO mice, have found that bone mass increased, and bone resorption (as assessed by N.Oc/B.Pm and Oc.S/BS) decreased, as a result of the aryl hydrocarbon receptordeficiency in AhR KO mice (5,6). On the other hand, using transgenic mice expressing constitutively active AhR, Wejheden C et al found that bone mass decreased in conjunction with an increase in bone resorption markers, which included protein levels of the osteoclast collagenase cathepsin K and serum level of C-telopeptide of type I collagen (CTX), in female transgenic mice (36). These data showed that AhR decreased bone mass by increasing bone resorption in vivo, and suggested that selective inhibition of the AhR pathway may increase bone mass through suppression of osteoclastic bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, c-Fos is required for the downstream induction of NFAT, cytoplasmic, calcineurin-dependent 1 (NFATc1) and fos-like Ag 1 (7,10). AhR 2/2 mice with systemic or osteoclast-specific deficiencies in AhR expression exhibit increased bone mass with decreased bone resorption (11)(12)(13), and bone resorption increases in mice overexpressing constitutively activated AhR (14). Evidence indicates that AhR is a positive regulator of osteoclastogenesis in vitro (11,12) and that AhR may mediate various activities of myeloid-lineage cells.…”
mentioning
confidence: 99%